Foreign direct investment and stock market development in Nepal - Keshab Khatri Chettri; Jeevan Kumar Bhattarai; Ramji Gautam (Asian Journal of Economics and Banking (AJEB), 2023)
Purpose -The purpose of this paper is to investigate the impact of foreign direct investment (FDI) on the stock market development in Nepal. Design/methodology/approach - The study used Johansen cointegration approach to determine long-run relationship and VEC Granger causality test to check the causal relations between the variables. The sample covered annual time-series data for the period 1996-2020. Findings - The results suggest that FDI plays significant positive role in the stock market development in the long-run but inversely affect in the short-run. Unidirectional causality running from FDI to stock market development is observed in the long-run and bidirectional in the short-run. There is an insignificant positive relationship between exchange rate and FDI in the short-run. Banking sector development complements stock market development in the short-run but act as a substitute in the long-run. The statistically negative coefficient of exchange rate imply that the appreciation of the home currency encourage the development of the stock market in the long-run. Originality/value - The positive and statistical coefficients of cointegration results indicate that FDI complements the development of stock market in Nepal in the long-run. Furthermore, the depreciation of the domestic currency may potentially contribute to the foreign direct investments in Nepal.
Keywords: 330; Cointegration; FDI; Johansen; Stock market development; Nepal